2013
DOI: 10.2308/bria-50415
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowing in Audit Firms: Organizational Response and Power Distance

Abstract: This paper investigates auditors' likelihood to report observations of colleagues' unethical behavior. We consider whether two characteristics that are particularly relevant to the audit environment, prior organizational response and power distance, affect willingness to report. Data collected from 106 senior-level auditors suggest auditors are more likely to report on their peers than on their superiors, but they are more likely to report superiors when prior organizational response is strong than when it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 37 publications
4
52
0
8
Order By: Relevance
“…Because of their disengagement from decisionmaking processes, individuals have little involvement with organizational issues and express their suggestions and concerns passively, resulting in acquiescent silence. According to Taylor and Curtis (2013), power distance is related to the desire to report unethical behavior of supervisors. Individuals in highpower-distance cultures are less inclined to challenge superiors' inappropriate attitudes, whereas individuals in a low-power-distance environment are more likely to challenge such inappropriate attitudes through speaking up (Goodwin & Goodwin, 1999).…”
Section: Power Distance and Silencementioning
confidence: 99%
“…Because of their disengagement from decisionmaking processes, individuals have little involvement with organizational issues and express their suggestions and concerns passively, resulting in acquiescent silence. According to Taylor and Curtis (2013), power distance is related to the desire to report unethical behavior of supervisors. Individuals in highpower-distance cultures are less inclined to challenge superiors' inappropriate attitudes, whereas individuals in a low-power-distance environment are more likely to challenge such inappropriate attitudes through speaking up (Goodwin & Goodwin, 1999).…”
Section: Power Distance and Silencementioning
confidence: 99%
“…However, given that the effects of these demographic variables remained unchanged (the significance and effects were highly similar), we did not explore again these controlling effects below (more complete tests are available upon request) (Kirkman et al 2009). In this study, we used power distance as a control variable because culture value orientations were considered as important predictors of employees' extra-role behaviors such as whistleblowing (Taylor and Curtis 2013). Power distance of employees and supervisors was assessed with a scale developed by Dorfman and Howell (1988), with the Cronbach's alpha respectively at 0.82 and 0.78.…”
Section: Control Variablesmentioning
confidence: 99%
“…They further conclude that the likelihood of reporting is lower with disclosed identity. In a more recent study by Taylor and Curtis (), it is found that ‘prior organisational response’ and ‘power distance’ are strongly related to intentions to report wrongdoing, as auditors are more likely to whistle‐blow on their peers than their superiors, and that they will also take into account the firm's reputation of responding to complaints when assessing personal costs. Seifert et al .…”
Section: Whistle‐blowing In An Auditing Contextmentioning
confidence: 99%